SPACIAL-TEMPORAL VARIABLES OF THE DOMINANT AND NON-DOMINANT INFERIOR MEMBER DURING THE KICK (Fiep Bulletin - online, 2015)
The soccer is one of the most practiced sports in the world and many studies have been focusing this modality, mainly the kick movement, which is decisive in this modality. This study had as objective to describe the kick kinematic variables executed by a right and a left-handed child doing the kick with its dominant and non-dominant members. Two male subjects, 10-years-old players of soccer, a right and a left-handed one, were analyzed. The subjects were instructed to try to get right a target, with one square meter positioned in the goal center. The kick was executed from the penalty mark. For data collection and analysis, Peak Motus system with two video cameras and frequency of images acquisition of 180 Hz was used. Three attempts of each member of each subject that got right the target were analyzed. The results showed that the non-dominant member presented similar characteristics to the dominant one and that when some results were compared to other studies they were different from the ones found in the consulted literature.
Keywords: soccer; kick; kinematics